Multiple contact zones and karyotypic evolution in a neotropical frog species complex - Souza, Lucas H. B. (2024)
Previous studies of DNA sequence and karyotypic data have revealed high genetic diversity in the Physalaemus cuvieri – Physalaemus ephippifer species complex—a group of small leptodactylid frogs in South America. To date, seven major genetic lineages have been recognized in this group, with species delimitation tests supporting four to seven of them as valid species. Among these, only P. ephippifer shows heteromorphic sex chromosomes, but the implications of cytogenetic divergence for the evolution of this group are unknown. We analyzed karyotypic, mitochondrial DNA, and 3RAD genomic data to characterize a putative contact zone between P. ephippifer and P. cuvieri Lineage 1, finding evidence for admixture and karyotypic evolution. We also describe preliminary evidence for admixture between two other members of this species complex—Lineage 1 and Lineage 3 of P. cuvieri. Our study sheds new light on evolutionary relationships in the P. cuvieri – P. ephippifer species complex, suggesting an important role of karyotypic divergence in its evolutionary history and underscoring the importance of hybridization as a mechanism of sex chromosome evolution in amphibians.